Методы построения микроэлектронных радиоизмерительных преобразователей с частотным принципом работы - Osadchuk, V. S.; Osadchuk, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Theoretical and experimental studies are presented on the dependence of the total resistance of transistor structures on the effects of temperature, light, pressure, and magnetic field. It is shown that the dependencies of the reactive component on the influence of the above factors are significant, which creates the prerequisites for the construction of microelectronic radio-measuring transducers. The conversion and sensitivity functions have been calculated and experimentally investigated. Recommendations for the design of transducers are provided.